Improvement of One-Dimensional Two-Fluid Momentum Conservation Equations for Vertically Stratified Flow. (2nd November 2018) - Heo, Jaeseok; Kim, Kyung Doo; Kim, Byoung Jae
Abstract: This paper deals with numerical challenges associated with simulating thermal-hydraulic phenomena in nuclear reactors with one-dimensional system analysis codes. The main focus of this research is directed toward assessment of the pressure gradient in vertically stratified flow, particularly the separate pressure drop effects for gas and liquid phases along the control cell. The pressure drop term in momentum conservation currently being developed based on the assumption of gas and liquid combined pressure drop was redefined such that two different pressures were imposed for gas and liquid separately. The verification of the proposed momentum equation for a vertically stratified flow was completed through simulations of the liquid velocity in a U-shaped manometer. Sensitivity analysis was also performed by increasing liquid mass in the pipe leading to different positions of the liquid-vapor interface from the bottom of each manometer pipe when the flow oscillation is stopped; i.e., the interfaces are not only cell boundaries but also various positions between cell edges. As a result, improved simulation results were obtained using the modified equations as it was indicated that the oscillation of fluid decays over time while the original solution for the large pipe does not converge to zero due to a mainly incorrect pressure drop term.